Tindak Pidana Peredaran Rokok Ilegal Perspektif Pertanggung Jawaban Pidana - Ahmad Yunus (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
Article 56 of Law number 39 of 2007 concerning Excise states that "any person who hoards, stores, owns, sells, exchanges, obtains or gives excisable goods which he knows or suspects originates from a criminal act based on this law shall be punished with criminal imprisonment for a minimum of 1 (one) year and a maximum of 5 (five) years and a fine of at least twice the excise value and a maximum of 10 (ten) times the excise value that should be paid." The circulation of illegal cigarettes can reduce the amount of tax revenue from tobacco products by the government. The circulation of illegal cigarettes in society is a form of crime that still needs attention because it is easy for us to encounter it without realizing it. Some goods subject to excise are tobacco products, in the form of cigarettes. Cigarettes are the result of tobacco processing which is popular with the public. Due to the large demand for cigarette production by the public and the high excise tax imposed by the government, many individuals try to avoid paying cigarette excise. Law enforcement and criminal responsibility are the main studies in this research.